Public preferences for wind farms involving electricity trade and citizen engagement in Ireland - Brennan, Noreen; van Rensburg, Thomas M. (Energy policy, 2020)
International trade in electricity from renewable sources can offer a flexible means by which EU member states can meet their country targets but to date in Ireland initiatives to build wind farms for export have been resolutely contested by affected communities. Using a discrete choice experiment (DCE), a survey of respondents living within 10 km of an existing wind farm is conducted to estimate the social impact of wind turbines designed to produce electricity for export under different levels of financial benefit and participation. Most respondents are willing to make trade-offs to allow for an export market but financial compensation required is greater for exports compared to domestic supply. Respondents prefer greater levels of participation than currently offered but favour moderate levels of participation in the absence of financial benefits. Respondents that had a positive experience of living next to an existing wind farm in terms of financial benefits, employment and community representation are generally more accepting of wind farms. Conversely, subjects with a strong sense of place attachment or a less convincing experience in terms of financial benefits and participation were less tolerant of wind farms and more likely to pick the status quo of no new wind farm development. •We estimate the social impact of wind energy exports on local residents in Ireland.•We examine the impact of local experience on attitudes to wind energy.•Distributive justice is found to be an important determinant of acceptance.•Moderate community engagement is preferred to more heavily involved participation.•Community representation and benefits based on setback distance are recommended.